An enhanced security alert system for smart home using IOT - Afshana Khanum; Rekha Shivakumar (Institute of Advanced Engineering and Science, 2019)
Today due to advancement in technology and Internet of Things, to deal with step-by-step jobs like mailing, accessing bank entries, watching degree of hotness and other jobs PCs were utilized. Because of fast improvement in IOT nowadays tablets, advanced mobile phones are utilized for such assignments [1]. Home security can be characterized as observing the home remotely located or centrally located. Today, home security is getting to be vital as the conceivable outcomes of interruption is expanding step by step, yet they have issues like postponement, non-web empowered and hard to deal. Intruder recognition is basic parts of home computerization and home security frameworks. Most generally, utilized specialized devices are mobile phones and sending mails are considered for controlling home appliances remotely by proposing productive structures. An Enhanced Security Alert System for Smart Home using IOT is composed in our proposed work. It identifies the intruder when no one is in home by sending alert message or caught picture to the proprietor (or) owner. Proposed framework is ease home security framework utilizes an IP Web-camera and Raspberry pi for limiting delay during the time of sending alert message. Fog Computing is incorporated to proposed framework to expand the level of security and limit the engendering delay. Proposed framework is to give minimal effort arrangement and adaptable association instrument for coordinating Internet of Things with home security frameworks.